The Impact of Visual Thinking Approach to Promote Elementary Students’ Problem Solving Skill in Mathemathics - Fendrik, Muhammad; Elvina, Elvina (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
This study aims to examine the influence of visual thinking learning to problem solving skill. Quasi experiments with the design of this non-equivalent control group involved Grade V students in one of the Elementary Schools. The design of this study was quasi experimental nonequivalent control group, the research bullet used the existing class. The results of research are: 1) improvement of problem soving skill. The learning did not differ significantly between students who received conventional learning. 2) there is no interaction between learning (visual thinking and traditional) with students' mathematical skill (upper, middle and lower) on the improvement of skill. 3) there is a difference in the skill of language learning that is being constructed with visual learning of thought in terms of student skill (top, middle and bottom).